The role and mechanism of pyroptosis and potential therapeutic targets in non-alcoholic fatty liver disease (NAFLD) - Li, Shu-Jing; Liu, An-Bu; Yu, Yuan-Yuan; Ma, Jin-Hai (Frontiers in Cell and Developmental Biology, 2024)
Abstract Non-alcoholic fatty liver disease (NAFLD) is a clinical pathological syndrome characterized by the excessive accumulation of fat within liver cells, which can progress to end-stage liver disease in severe cases, posing a threat to life. Pyroptosis is a distinct, pro-inflammatory form of cell death, differing from traditional apoptosis. In recent years, there has been growing research interest in the association between pyroptosis and NAFLD, encompassing the mechanisms and functions of pyroptosis in the progression of NAFLD, as well as potential therapeutic targets. Controlled pyroptosis can activate immune cells, eliciting host immune responses to shield the body from harm. However, undue activation of pyroptosis may worsen inflammatory responses, induce cellular or tissue damage, disrupt immune responses, and potentially impact liver function. This review elucidates the involvement of pyroptosis and key molecular players, including NOD-like receptor thermal protein domain associated protein 3(NLRP3) inflammasome, gasdermin D (GSDMD), and the caspase family, in the pathogenesis and progression of NAFLD. It emphasizes the promising prospects of targeting pyroptosis as a therapeutic approach for NAFLD and offers valuable insights into future directions in the field of NAFLD treatment.